Merger Clauses in Contracts Governed by Polish Law - Strugała, Radosław (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The use of so-called merger clauses while drafting contracts governed by the civil law is becoming increasingly popular. Since merger clauses originated from the common law, it is not easy to ascertain their legal effects under the civil law. This is also the case in Polish law. Not only is there little mention in the legal literature of the effects of merger clauses, but also legal scholars' views on the issue differ widely.This article tries to answer the question of what the legal effects of using merger clauses under Polish law are. Among others, it tackles the important issue of how a merger clause inserted into a contract influences the process of its interpretation and closing its loopholes. Moreover, it attempts to compare merger clauses' legal effects under Polish law and European private law model rules. The starting point of the analysis performed in the paper is the distinction between two functions of contractual clauses, which leads to a clearer description of the consequences of merger clauses' usage. The adoption of the aforementioned distinction leads to the conclusion that the legal effects of merger clauses under Polish law may be far more significant than is often considered. Additionally, it can be observed that these effects do not differ from the legal effects of merger clauses under European law model rules as much as has been claimed.
Keywords: prawo polskie; umowy; klauzula dotycząca fuzji